2020
DOI: 10.1128/mbio.01127-20
|View full text |Cite
|
Sign up to set email alerts
|

The Novel J-Domain Protein Mrj1 Is Required for Mitochondrial Respiration and Virulence in Cryptococcus neoformans

Abstract: The opportunistic fungal pathogen Cryptococcus neoformans must adapt to the mammalian environment to establish an infection. Proteins facilitating adaptation to novel environments, such as chaperones, may be required for virulence. In this study, we identified a novel mitochondrial co-chaperone, Mrj1 (mitochondrial respiration J-domain protein 1), necessary for virulence in C. neoformans. The mrj1Δ and J-domain-inactivated mutants had general growth defects at both routine laboratory and human body temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 84 publications
1
31
0
Order By: Relevance
“…factors for C. neoformans, the polysaccharide capsule and cell wall melanin. Other studies have linked mitochondria function to capsule formation including a demonstration that the ETC inhibitors rotenone, SHAM, and antimycin A reduced capsule size [15,16] (Fig 2). Overall, these studies in C. albicans and C. neoformans illustrate the complex impact of mitochondrial functions on the ability of these fungi to cause disease.…”
Section: The Electron Transport Chain Is Connected To Fungal Pathogenesismentioning
confidence: 97%
See 2 more Smart Citations
“…factors for C. neoformans, the polysaccharide capsule and cell wall melanin. Other studies have linked mitochondria function to capsule formation including a demonstration that the ETC inhibitors rotenone, SHAM, and antimycin A reduced capsule size [15,16] (Fig 2). Overall, these studies in C. albicans and C. neoformans illustrate the complex impact of mitochondrial functions on the ability of these fungi to cause disease.…”
Section: The Electron Transport Chain Is Connected To Fungal Pathogenesismentioning
confidence: 97%
“…neoformans , the polysaccharide capsule and cell wall melanin. Other studies have linked mitochondria function to capsule formation including a demonstration that the ETC inhibitors rotenone, SHAM, and antimycin A reduced capsule size [ 15 , 16 ] ( Fig 2 ). Overall, these studies in C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the cytosolic JDP, Ydj1, contributes to the stress response, morphogenesis, and mitochondrial function of C. albicans [ 67 ]. Furthermore, the mitochondrial JDP, Mrj1, contributes to mitochondrial respiration, capsule formation, and ultimately virulence in C. neoformans [ 68 ]. Surprisingly there are few other reports on the roles of JDPs in the virulence of human fungal pathogens despite their well characterized roles in fungal pathogens of insects [ 69 , 70 ] and plants [ 71 , 72 , 73 , 74 , 75 ].…”
Section: Major Classes Of Hspsmentioning
confidence: 99%
“…The ability to make fungal selective inhibitors of Hsp90s is critical to ensuring that they can be used safely without off target effects. Studies characterizing chaperones contributing to virulence in fungal pathogens have identified divergent components of the chaperone network in fungi such as the sHSPs [ 99 ] and JDPs [ 68 ]. This information may be exploited to prioritize these divergent targets for antifungal drug development.…”
Section: Heat Shock Proteins As Drug Targets For Fungal Pathogensmentioning
confidence: 99%